Pengaruh Kinerja Keuangan Terhadap Indeks Saham Syariah Indonesia Tahun 2018 – 2022 - Nianti, Eni (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2024)
This research aims to determine the influence of Net Profit Margin (NPM), Return on Investment (ROI), Return on Equity (ROE), and Earning per Share (EPS) simultaneously/together on the Indonesian Sharia Stock Index for 2018-2022 . The population and research sample were 25 companies. The sampling technique uses a Non-Probability Sampling technique, namely; with a purposive sampling technique. The analysis in this research uses the e-views (econometrics views) software program version 12. The research method used is qualitative research using a descriptive approach. Partial results on the Net Profit Margin (NPM) variable show that there is no influence of NPM on the Indonesian Sharia Stock Index.The Return on Investment (ROI) variable shows that there is no influence of Return on Investment on the Indonesian Sharia Stock Index. The Return on Equity (ROE) variable shows that there is no influence of Return on Equity on the Indonesian Sharia Stock Index. The Earning per Share (EPS) variable shows that there is no influence of Earning per Share on the Indonesian Sharia Stock Index. Simultaneous results show that there is an influence of Net Profit Margin (NPM), Return on Investment (ROI), Return on Equity (ROE), and Earning per Share (EPS) simultaneously/together on the Indonesian Sharia Stock Index.Based on the results of the coefficient of determination test, it shows that the Adjusted R square value is 0.119662 or 11.9662%. This means that the variables Net Profit Margin (X1), Return on Investment (X2), Return on Equity (X3) and Earning per Share (X4) for the Indonesian Sharia Stock Index (Y) are 11.9662 % while the remaining 88.0338% is influenced by other variables.